(untitled) (ҚазҰУ хабаршысы. Экология сериясы, 2019)
The analysis of a current state of energy and ecological sector of Kazakhstan which is carried out according to basic provisions «The global energy and ecological strategy of a sustainable development in the XXI century» presented in the book of the President of the Republic of Kazakhstan N. A. Nazarbayev is provided inthis paper. The energy sector represents the leading unit of social and economic life of Kazakhstan, a basis of its fuel and energy complex (FEC). On a condition of energy industry the territory of the country can be divided conditionally into 3 zones: northern, western and southern. The balance of power of the electric energy on zones is given. The share of various types of power plants and a ratio of the used resources for generation of an electric energy in Kazakhstan is shown. Power plants are classified by national, industrial and regional value. The main features of structure of a power complex of Kazakhstan, prospects of using alternative resources of energy are marked out. Preservation of technological balance «traditional power – renewable» consists in strategic planning of system of national and international energy and ecological safety. Key words: fuel and energy complex, power plants, energy, ecology, energy and ecological strategy, alternative resources of energy, устойчивое развитие, Kazakhstan.